Administration of Topical Passion Fruit Extract Cream (Passiflora edulis) inhibits the Increase of MMP-1 Levels and Decreases the Amount of Collagen in Wistar Rats (Rattus norvegicus) Exposed to UV-B Rays - Anak Agung Gde Putra Wiraguna (Journal of Global Pharma Technology, 2019)
Introduction: Aging skin is most prevalent due to exposure to sunlight, especially UV-B rays. UV-B rays which stimulate the formation of free radicals are highly reactive molecules with unpaired electrons that can cause elevated levels of MMP-1, causing a decrease in the amount of skin collagen. This study was an experimental animal study with a post-test only control group design.  Method: A total of 36 Wistar rat were divided into 2 groups, each consisting of 18 Wistar rat, the control group was smeared with placebo cream and the treatment intervention group was smeared with passion fruit seed extract cream 100%, all groups were exposed to UV-B with a total dose of 840 mJ / cm ² for 4 weeks, then an excision was carried out for the examination of dermis collagen amount and level of MMP-1.  Result: The results of the comparative analysis of the two groups using independent t-test showed that there were significant differences between the two groups, the mean level of MMP-1 and the mean amount of collagen with p <0.05. The mean level of MMP-1 and the mean amount of collagen treatment in intervention group were 2.32% and 70.32%, and control group showed the mean level of MMP-1 and the average amount of collagen at 2.99% and 63.63% respectively.  Conclusion: the administration of passion fruit seed extract cream inhibited the increase of level of MMP-1 and the decrease of total collagen level in Wistar rat skin was exposed to UV-B.Keywords: Passion fruit, MMP-1, collagen, Skin.